Identifikasi kesulitan belajar matematika di rumah selama pandemi covid-19 pada siswa kelas IV Sekolah Dasar - Ika Berliana Fauziah; Sukarno Sukarno; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2021)
Abstract. This research aims to describe the aim of this research is to identify difficulties in learning mathematics at home during the Covid-19 pandemic which took place in grade 4th elementary school. The research focus in writing this thesis is the method used in this research is descriptive qualitative with a phenomenological approach. The data sources of this research were all 4th students, parents, and 4th students teachers. The data collection technique was done by using questionnaires, interviews, and documentation studies. The data validity test used in this study was technical triangulation and source triangulation. Data were analyzed using the data analysis model Miles and Huberman. The results of this study indicate that student learning problems occur because students have difficulty understanding concepts, difficulty solving problems in story problems, and difficulties in numeracy skills. The difficulty in understanding the concept is as much as 78%, the difficulty in solving a story problem is as much as 90%, and the difficulty in calculating in number operations is as much as 85%. The problems that occur are caused by several factors. Factors from within students and outside students. seen from these factors, efforts can be made to solve learning difficulties experienced by students by doing remedies, doing exercises, taking private lessons, and maintaining communication with the teacher.